Μανώλης Αγγελάκης (gr) ΤΙΝD Tind, τίποτα δεν είναι σχεδιασμένο. Print what you love – love what you print. - Panayides, Angelos (My University, 2026)
Screenprinting workshop lay Manolis Angelakis (TIND) using stencils, exploring traditional techniques without emulsion.